(3eLehYI LGeYI eMGSf GdCTYGQ ef cd eYfi MSf efJNH eNJGQs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s
(3ChdgG (B:s
(3hQOJ QbYI fUgG HYO GdHSedI GdeSFhd ef GdSGOI GdCYjGf, bhd GdHMJQj(B: (3hdjdI ghefG Ydi GdYjS CQSdJ HWja NjGd ojTHog GdMb HGWdg s
(3BNQgG (B:s
(3ceGdc TGgOJ GdLeGd HCSQg eLGRj hEWdGb GdceGd MbjbJj s
(3JQJjH ChQGbgG eVWQHIs
(3HHYV ChQGbgG JXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B195 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs